2023
DOI: 10.3389/fphar.2023.1163115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular vasculogenic mimicry–Related signatures predict clinical outcomes and therapeutic responses in bladder cancer: Results from real-world cohorts

Abstract: Bladder cancer (BLCA) is a heterogeneous disease, and there are many classical molecular subtypes that reflect tumor immune microenvironment (TME) heterogeneity but their clinical utility is limited and correct individual treatment and prognosis cannot be predicted based on them. To find reliable and effective biomarkers and tools for predicting patients’ clinical responses to several therapies, we developed a new systemic indicator of molecular vasculogenic mimicry (VM)–related genes mediated by molecular sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Siglec15, a member of the sialic acid-bound immunoglobulin-like lectin family, is an emerging broad-spectrum target for normalizing cancer immunotherapy (113). Jiao et al found that BCa patients in the high Siglec15 group were more sensitive to targeting vascular mimicry-related signaling pathways (b-catenin, PPAR-g, and FGFR3 pathways) (114,115). Therefore, Siglec15 may be used as an indicator of targeted therapy for VM.…”
Section: Vasculogenic Mimicry In Bladder Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Siglec15, a member of the sialic acid-bound immunoglobulin-like lectin family, is an emerging broad-spectrum target for normalizing cancer immunotherapy (113). Jiao et al found that BCa patients in the high Siglec15 group were more sensitive to targeting vascular mimicry-related signaling pathways (b-catenin, PPAR-g, and FGFR3 pathways) (114,115). Therefore, Siglec15 may be used as an indicator of targeted therapy for VM.…”
Section: Vasculogenic Mimicry In Bladder Cancermentioning
confidence: 99%
“…In BCa, DNA methylation plays a key role in early diagnosis, predicting prognosis, predicting therapeutic opportunities, and serving as a potential therapeutic target (116), 5-Methylcytosine (5mC) in DNA is the most important epigenetic modification that shapes TME by influencing genomic stability, determining cancer cell differentiation status, and selecting cell identity (117,118). Jiao et al found that the high 5 mC score group may not be sensitive to neoadjuvant chemotherapy, but there are several immunosuppressive oncogenic pathways significantly enriched in the heterogeneous high 5 mC score group associated with VM, including WNT-b-catenin network, FGFR3 network, and VEGFA (114,(119)(120)(121). These VM pathways may provide promising therapeutic opportunities for BLCA patients in the high 5mC scoring group.…”
Section: Vasculogenic Mimicry In Bladder Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…The highest incidence of bladder cancer currently falls in most developed regions of the world, with approximately 550,000 new cases each year [ 4 ]. BLCA is a heterogeneous disease, comprising several tumor subtypes with differences in histology, genomic aberrations, and prognosis [ 5 ]. The mode of cell death has an important role in the development of BLCA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%